Imagery and Metaphorical Expressions of Love in Ed Sheeran’s “Thinking Out Loud” - Sihotang, Tiodor; Anggita Ristia Damanik, Bernieke (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study investigates the application of imagery and metaphor in Ed Sheeran’s song Thinking Out Loud as a medium for expressing the concept of love. Utilizing a descriptive qualitative methodology within the framework of conceptual semantics, the research examines the role of figurative language in conveying emotional meaning. The analysis uncovers the use of diverse imagery types including visual, kinesthetic, and tactile as well as several conceptual metaphors, such as love is a journey, love is physical strength, and love is time. These figurative devices serve to deepen the emotional resonance and conceptual understanding of love in the song, thereby reinforcing its effectiveness in articulating intimate human experiences.